Proceedings of the International Seminar on Promoting Local Resources for Sustainable Agriculture and Development (ISPLRSAD 202 2021
DOI: 10.2991/absr.k.210609.068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quality and Land Characteristics That Control Local Maize Production in Gorontalo

Abstract: Increase national maize production has not been followed by an increase in maize productivity per unit area because maize was grown on land that was not suitable with these land quality. This study aims to determine the land quality that control of local maize production. This research was conducted at the Gorontalo Regency. A total of 33 mapping units had been established containing data of soil properties, climate and terrain divided into land quality, as well as data of local maize production. A partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
5
0
5
Order By: Relevance
“…Jagung mengandung karbohidrat, protein dan lemak yang tinggi, sehingga berpotensi menjadi bahan pangan pokok dan sumber pangan fungsional (Lalujan et al 2017). Peningkatan produktivitas jagung merupakan salah satu faktor utama dalam pengembangan tanaman pangan (Nurdin et al, 2021). Jagung di Indonesia ditanam pada agroekosistem yang beragam, mulai dari lingkungan berproduksi tinggi sampai yang berproduktivitas rendah yang menjadikan produktivitas tidak maksimal, sehingga diperlukan teknologi produksi spesifik lokasi sesuai dengan kondisi lingkungan setempat (Zubachtirodin et al, 2008).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Jagung mengandung karbohidrat, protein dan lemak yang tinggi, sehingga berpotensi menjadi bahan pangan pokok dan sumber pangan fungsional (Lalujan et al 2017). Peningkatan produktivitas jagung merupakan salah satu faktor utama dalam pengembangan tanaman pangan (Nurdin et al, 2021). Jagung di Indonesia ditanam pada agroekosistem yang beragam, mulai dari lingkungan berproduksi tinggi sampai yang berproduktivitas rendah yang menjadikan produktivitas tidak maksimal, sehingga diperlukan teknologi produksi spesifik lokasi sesuai dengan kondisi lingkungan setempat (Zubachtirodin et al, 2008).…”
Section: Pendahuluanunclassified
“…Salah satu sentra produksi jagung di wilayah Kabupaten Gorontalo dan masih dijumpai petani yang menanam jagung lokal adalah Kecamatan Mootilango. Eksistensi jagung lokal Gorontalo mulai punah karena petani lebih memilih menanam jagung hibrida dengan program subsidi benih jagung gratis dari Pemerintah (Nurdin et al 2021). Selain karena produktivitas jagung lokal yang rendah (Sirappa dan Syamsuddin 2015) petani juga membudidayakan jagung pada lahan berlereng yang rentan terjadinya degradasi lahan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Tis country ranked 8th among the maize-producing nations with a contribution of 2.19% and 2.42% of the world's total harvested area [5]. However, the main problem is the relatively low level of yield in several regions because the achievement of maize production has not been followed by an increase in yield per unit area [6]. Tis is indicated by the average yield in 2020, which was up to 5.57 ton/ha [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tis indicated that the productivity of hybrid maize is still higher than local maize [18], but with lower achievement compared to the national maize production of 5.57 tons/ha [5], and has not yet reached the target of 5.60 tons/ha in 2021 [19]. Te production of hybrid maize in Gorontalo can reach 9.78-13.11 tons/ha [20] because it is often cultivated on land that does not meet the required qualities [6]. Terefore, there is a need to determine land quality-based hybrid maize land suitability criteria for site-specifc land use planning in Boalemo District.…”
Section: Introductionmentioning
confidence: 99%